Performance of Philippine initial public offerings critique of current studies and update - Unite, Angelo A. (1998)
This paper investigams the short- and long-run performance of Philippine Initial Public Offerings (IPOs) from 1987 to 1997. We compare our results to those in papers published in Philippine journals and discuss the shortcomings of these previous studies. Based on our results, we ﬁnd that past researchers may have inadequately studied market price reactions to IPOs, and that IPOs earn, on average, returns of 22.69 percent on the initial trading day. Over a three-year aftermarket period, returns total 48.33 percent or 5.44 percent less than a matched set of publicly-traded firms. This suggests that although investors in Philippine IPOs make signiﬁcant returns on the initial trading clay, if they hold stock of IPOs for a long period, they earn slightly lower average returns than if they had held other comparable stocks. We think that our estimates are derived in a manner consistent with international ﬁnancial market studies and that these results may be a more accurate depiction of actual performance of Philippine IPOs.
Includes bibliographical references (page 207).